Artificial Intelligence for Digitising Industry - Applications. - Vermesan, Ovidiu. (River Publishers, 2021)
This book provides in-depth insights into use cases implementing artificial intelligence (AI) applications at the edge. It covers new ideas, concepts, research, and innovation to enable the development and deployment of AI, the industrial internet of things (IIoT), edge computing, and digital twin technologies in industrial environments.